2021
DOI: 10.1016/j.ekir.2020.11.034
|View full text |Cite|
|
Sign up to set email alerts
|

Roxadustat for CKD-related Anemia in Non-dialysis Patients

Abstract: Introduction Roxadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor that stimulates erythropoiesis and improves iron metabolism. We assessed the efficacy and tolerability of roxadustat in patients with chronic kidney disease (CKD)-related anemia not on dialysis. Methods ANDES was a global Phase 3 randomized study in which adults with stage 3–5 CKD not on dialysis received roxadustat or placebo. Patients were initially dosed thrice weekly; dose was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 34 publications
5
109
0
Order By: Relevance
“…Roxadustat Increased the Level of Hemoglobin in Non-Dialysis-Dependent Chronic Kidney Disease Patients With Elevated C-reactive Protein Levels Inflammation, which causes iron retention, increased hepcidin formation and impaired erythroid progenitor proliferation was believed as a major contributing factor to anemia (Macdougall et al, 2016;Weiss et al, 2019). In order to assess the influence of inflammation on the effect of roxadustat, we extracted Hb changes in subjects with baseline CRP > ULN from six trials (Chen et al, 2019a;Akizawa et al, 2019c;NCT02174731, 2020;Coyne et al, 2021;Fishbane et al, 2021;Provenzano et al, 2021) (four trials for DD-CKD patients, two trials for NDD-CKD patients). The pooled results showed that for patients with baseline CRP upper than ULN, there was a significant rise of Hb level with the use of roxadustat compared with ESAs and placebo (WMD: 0.63; 95% CI: 0.09-1.17; p 0.02; with heterogeneity [p < 0.00001]; Figure 5 and Table 3).…”
Section: Comparison Of Effects On Iron Utilization Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Roxadustat Increased the Level of Hemoglobin in Non-Dialysis-Dependent Chronic Kidney Disease Patients With Elevated C-reactive Protein Levels Inflammation, which causes iron retention, increased hepcidin formation and impaired erythroid progenitor proliferation was believed as a major contributing factor to anemia (Macdougall et al, 2016;Weiss et al, 2019). In order to assess the influence of inflammation on the effect of roxadustat, we extracted Hb changes in subjects with baseline CRP > ULN from six trials (Chen et al, 2019a;Akizawa et al, 2019c;NCT02174731, 2020;Coyne et al, 2021;Fishbane et al, 2021;Provenzano et al, 2021) (four trials for DD-CKD patients, two trials for NDD-CKD patients). The pooled results showed that for patients with baseline CRP upper than ULN, there was a significant rise of Hb level with the use of roxadustat compared with ESAs and placebo (WMD: 0.63; 95% CI: 0.09-1.17; p 0.02; with heterogeneity [p < 0.00001]; Figure 5 and Table 3).…”
Section: Comparison Of Effects On Iron Utilization Parametersmentioning
confidence: 99%
“…In addition, the duration of the studies enrolled in previous meta-analyses was relatively short, with a maximum follow-up of 26 weeks. Recently, the results of five large phase 3 clinical trials Akizawa et al (2020a), Coyne et al (2021), Fishbane et al (2021), Provenzano et al (2021), Shutov et al (2021) of roxadustat were released, so we updated the meta-analysis. Randomized controlled trials that assessed the efficacy (hemoglobin levels and response) and safety (treatment-emergent adverse events) of roxadustat in DD-CKD and NDD-CKD anemia patients comparing with ESAs or placebo were retriedved with an aim to generate a robust conclusion on the effect of and safety of roxadustat.…”
Section: Introductionmentioning
confidence: 99%
“…47 The global phase 3 program for roxadustat includes 4 studies in NDD-CKD patients (ALPS, ANDES, and OLYMPUS using placebo control; DOLOMITES using ESA control) and 4 studies in DD-CKD patients (HIMALAYAS, ROCKIES and SIERRAS using epoetin control; PYRENEES using epoetin or darbepoetin control). The first two publications 48,49 from the roxadustat global phase 3 program appeared in Kidney International Reports in 2021, accompanied by an editorial. 50 In the ANDES study of NDD-CKD patients 48 915 subjects were randomized 2:1 to roxadustat or placebo.…”
Section: Roxadustatmentioning
confidence: 99%
“…Several of these agents have global development programs with sufficient statistical power to examine major cardiovascular events (MACE) versus comparator (ESA or placebo). The first 2 publications from these global studies appeared in Kidney International Reports earlier in 2021 and addressed the safety and efficacy of roxadustat in non-dialysis dependent (NDD)-CKD 2 and incident dialysis 3 patients. The NDD-CKD study demonstrated roxadustat to have superior efficacy and noninferior safety to placebo.…”
mentioning
confidence: 99%
“…The NDD-CKD study demonstrated roxadustat to have superior efficacy and noninferior safety to placebo. 2 The incident dialysis patient study demonstrated roxadustat to have noninferior efficacy and superior safety (MACE) to ESA. 3 These 2 reports were accompanied by a commentary by Winkelmayer and Walther titled "Roxadustat for CKD Anemia-Starting the Jigsaw Puzzle, What Will the Finished Picture Show?"…”
mentioning
confidence: 99%